Effects of Electrical Stimulation with Different Impulses on Physical Characteristics of Rabbit Meat - Yurmiati, H; Wiedy, GA; Kusmajadi, S (ANIMAL PRODUCTION, 2010)
Meat becoming less tender with age. One of the methods to increase the meat tenderness is by electrical simulation. The objective of this study was to investigate the effect of electrical simulation with different level of impulses on physical characteristics of rabbit meat. Twenty carcasses of Flemish Giant rabbit were randomly subjected into four differents treatments (impulse levels), which were control, impulse 25, impulse 50, and impulse 75. Each treatmentÂ  was repeated 5 times. Measured variables were pH, tenderness, water holding capacity, and cooking lose. The results showed that different levels of electrical stimulation had significant effects on the physical characteristics of rabbit meat.Â Higher impulse level caused lower ultimate pH and more tender meat. Overall, the best physical characteristics of rabbit meat was obtained from electrical stimulation with impulse level of 50. (Animal Production 12(2): 124-127 (2010)Key Words : electrical stimulation, tenderness, rabbit, meat